SIKAP KAUM MUDA PERANTAU ASAL MANGGARAI DI BALITERHADAP PRAKTEK BELIS KEKINIAN - Eden, Antonius Setiarja; Kebayantini, Ni Luh Nyoman; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
Belis is dowry as a prerequisite for men in Manggarai customary marriage. Belis is interpreted as a tribute to a woman's womb (mother), a form of responsibility of a man and willing to show that men have been able to foster a household.As time goes by, especially the magnitude of capitalist influence that drives materialistic concepts, culture cannot escape from it. The meaning and symbol of belis has changed that actually impacts on the essence of itself. The current meaning of belis is no more than culture balance sheet to measure the status of women. Thus, the slogan “the higher of (education, social and economic of women/parents) the status, the greater belis demanded. On this phenomenon, Manggarainese youth should declare their perspective to place the meaning of belis on its origin.The main purpose of the study is to know and to map Manggarianese youth perspective in Bali on current practice of belis. Nowadays, practice of belis is far from meaning and symbol as original pattern of belis. Symbols (material) of belis tend to be determinant of the status of women. Appreciation is ambiguous and vague. The result of the study that Manggarainese youth in Bali have different attitudes and actions on current practice of belis. Their attitudesare to accept, reject and criticize the current practice of belis. Manggarainese youth who accept belis provide rational reason in which it related to increasing of need. The refusal side provide irrational reason in which belis is used to measure high-low social status of women. Key words: Manggarainese belis tradition, front stage and backstange of belis.